Muslim Rimba: Dialectic of Indigenous Belief Bukit Dua Belas National Park (TNBD) Jambi - Ramli, Supian; Muspawi, Mohammad; Rahman, K.A.; Sobri, Muhammad; Rafi’i, Muhammad (Indonesian Journal of Islamic Education and Local Culture, 2023)
Islam is the universal belief of mankind and as a dialogical religion is able to interact with various beliefs, various cultures and local traditions that develop in a multicultural society such as Indonesia. "Muslim Rimba" is associated as a religious subject who can reconcile the interpretation of Islamic teachings into local beliefs or the Religion of Rimba. An ethnographic approach was used in this study. Descriptions of observations, source interviews and participatory experiences are the strengths it. The findings of this study indicate after to be a Muslim Rimba view that the rituals and beliefs of rimba people are still carried out as a form of acculturation and respect for the teachings of indigenous peoples without leaving the commandments of the religious law they adhere to. The Muslim Rimba consistently participated in rituals such as Godong (Bebalai and Mandiko Budak); Sedang (Bedikir, Ngicap Rapah, Melantok Kedundung and Orang Beranok) and Kecik (Nyambatko Tuhan, Pepatiah Budak and Sanggokko).